Gender effects in anaesthesia training in Australia and New Zealand. (March 2020) - Pearce, Greta; Sidhu, Navdeep; Cavadino, Alana; Shrivathsa, Archana; Seglenieks, Richard
Abstract: Background: Women face gender-based challenges in their medical education and career. Inequitable access to procedural training, a confidence gap, and professional identity deficit have been shown. We made a gender comparison of procedural case volume, confidence for independent practice, perceived gender and ethnic bias, and professional identity in Australasian anaesthesia trainees. Methods: An online, voluntary, anonymous survey using SurveyMonkey® was delivered to Australasian anaesthesia trainees. Information collected included demographics, experience and confidence in 12 anaesthetic procedures, assessments relating to confidence and professional identity, and perceived gender and ethnic bias. Gender differences were evaluated. Results: Three hundred and fifty-six trainees (22.2%) of the Australian and New Zealand College of Anaesthetists (ANZCA) responded. Male trainees reported a higher number (standard deviation) of procedures performed greater than 10 times (men 4.45 [2.55], women 3.78 [1.95]; P <0.001 adjusted for training level). Men were more likely to rate themselves at a training competency above their actual training level (men 18.6%, women 7.8%; P =0.004) and exaggerate procedural experience to supervisors (men 30.8%, women 11.8%; P <0.001). Final-year male trainees felt significantly more prepared for independent practice ( P =0.021, trend across ordered responses). Women reported significantly higher levels of gender bias exhibited by patients (men 1.1%, women 84.5%; P <0.001) and in training overall (men 10.3%, women 55.3%; P <0.001), which was compounded in women with an ethnic minority background. Conclusions: A discrepancy exists between the number of procedures performed by male and female anaesthesia trainees in Australia and New Zealand. Relative male overconfidence may be a major contributing factor to the gender confidence gap.